FOUR CHALLENGES OF LONG-TERM SOCIO-ECOLOGICAL RESEARCH IN BRAZIL - Oliveira, Jose Gilmar (Associação Brasileira de Ciência Ecológica e Conservação (ABECO), 2020)
Long Term Ecological Research (LTER) aims to monitor natural ecological processes that operate over longer time periods than are typically permitted by standard research grants (e.g. species life cycles, natural resource dynamics, and the ecological effects of climate changes). Despite the enormous success of LTER, many of the initial projects largely overlooked the consequences of their study sites being embedded in wider socio-ecological systems. This potential shortcoming led to the development of Long Term Socio-Ecological Research (LTSER), a logical extension of LTER that seeks to fully integrate the human dimension into long term environmental monitoring. LTSER sites have now been successfully established in many countries, although such an approach is still incipient in Brazil´s program of LTER (known by the acronym PELD in Portuguese).  The PELD APA Costa de Corais is one of Brazil’s newest PELD sites, and intentionally incorporated a strong socio-ecological focus into its design and implementation. In this brief perspective we draw on our experiences of creating a LTSER, identifying four key challenges that need to be overcome to ensure successful implementation.